2006
DOI: 10.1001/jama.295.19.2286
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Spinal Cerebrospinal Fluid Leaks and Intracranial Hypotension

Abstract: Spontaneous intracranial hypotension is not rare but it remains underdiagnosed. The spectrum of clinical and radiographic manifestations is varied, with diagnosis largely based on clinical suspicion, cranial magnetic resonance imaging, and myelography. Numerous treatment options are available, but much remains to be learned about this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
1,079
3
33

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 909 publications
(1,136 citation statements)
references
References 114 publications
(118 reference statements)
21
1,079
3
33
Order By: Relevance
“…The CSF pressure of SIH patients with a long duration of symptoms was higher than of those with a short duration. We found that in several cases, the initial CSF OP was lower than 60 mmH 2 O, while the follow-up value elevated to within the normal range, which may be explained by compensatory mechanisms (Schievink, 2006;2008;Mokri, 2013;Kranz et al, 2015;Limaye et al, 2016). In the case of CSF leakage, the volume of CSF decreased as a result.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The CSF pressure of SIH patients with a long duration of symptoms was higher than of those with a short duration. We found that in several cases, the initial CSF OP was lower than 60 mmH 2 O, while the follow-up value elevated to within the normal range, which may be explained by compensatory mechanisms (Schievink, 2006;2008;Mokri, 2013;Kranz et al, 2015;Limaye et al, 2016). In the case of CSF leakage, the volume of CSF decreased as a result.…”
Section: Discussionmentioning
confidence: 73%
“…The acronym SEEPS can be used to summarize the typical MRI features: subdural fluid collections, enhancement of pachymeninges, engorgement of venous structures, pituitary enlargement, and sagging of the brain (Schievink, 2006;Spears, 2014;Limaye et al, 2016). The mechanisms of these abnormalities can be well explained by the Monro-Kellie hypothesis (Mokri, 2001;2004;2013;Limaye et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations